A penalty-based scaling algorithm for the multi-period multi-product distribution planning problem. Issue 4 (3rd April 2017) - Ahmad Hosseini, S.; Şahin, Güvenç; Ünlüyurt, Tonguç
ABSTRACT: Multi-period multi-product distribution planning problems are depicted as multi-commodity network flow problems where parameters may change over time. The corresponding mathematical formulation is presented for a discrete time setting, and it can also be used as an approximation for a continuous time setting. A penalty-based method which employs a cost-scaling approach is developed to solve some auxiliary penalty problems aiming to obtain an optimal solution for the original problem. The experiments on both random instances and case study problems show that the algorithm finds good-quality solutions with reasonable computational effort.